Associations of physical activity, sedentary time, and physical fitness with mental health during pregnancy: The GESTAFIT project - María Rodriguez-Ayllon; Pedro Acosta-Manzano; Irene Coll-Risco; Lidia Romero-Gallardo; Milkana Borges-Cosic; Fernando Estévez-López; Virginia A. Aparicio (Elsevier, 2021)
Purpose: This study was aimed to analyze the associations of objectively measured physical activity (PA), sedentary time, and physical fitness with mental health in the early second trimester (16 ± 2 gestational weeks) of pregnancy. Methods: From 229 women initially contacted, 124 pregnant women participated in the present cross-sectional study. Data were collected between November 2015 and March 2017. The participants wore Actigraph GT3X+ Triaxial accelerometers for 9 consecutive days to objectively measure their PA levels and sedentary time. A performance-based test battery was used to measure physical fitness. Self-report questionnaires assessed psychological ill-being (i.e., negative affect, anxiety, and depression), and psychological well-being (i.e., emotional intelligence, resilience, and positive affect). Linear regression analyses were adjusted for age, educational level, accelerometer wear time, miscarriages, and low back pain. Results: Moderate-to-vigorous PA was negatively associated with depression (β = -0.222, adjusted R2 = 0.050, p = 0.041). Higher levels of sedentary time were negatively associated with positive affect (β = -0.260, adjusted R2 = 0.085, p = 0.017). Greater upper-body flexibility was positively associated with better emotional regulation (β = 0.195, adjusted R2= 0.030, p = 0.047). The remaining associations were not significant (all p > 0.05). Conclusion: An active lifestyle characterized by higher levels of moderate-to-vigorous PA and lower levels of sedentary time during pregnancy might modestly improve the mental health of pregnant women. Although previous research has focused on the benefits of cardiorespiratory exercise, the present study shows that only upper-body flexibility is related to emotional regulation in early pregnant women. If the present findings are corroborated in further experimental research, physical exercise programs should focus on enhancing flexibility to promote improvements in emotional regulation during early second-trimester of pregnancy.